JEWGIENIJ IWANOWICZ ZAMIATIN JAKO PREKURSOR XX-WIECZNEJ POWIEŚCI ANTYUTOPIJNEJ - Brinko, Alena (Studia Europaea Gnesnensia, 2018)
The aim of this article is to reveal the relationship between the author of the first dystopia, Yevgeny Zamyatin and a totalitarian regime, by means of analyzing the biography and selected works of that writer; the analysis of the novel We – a prophecy novel, which can be regarded as an exaggerated depiction of the Stalinist regime; the analysis of the influence Zamyatin’s novel had on – far more famous – works by George Orwell and Aldous L. Huxley, as well as on the anti-utopia genre (dystopian literature) in general.